Assessing the impact of environmental, occupational health and safety, and food safety management systems on the sustainable performance of food processing companies - Hayat, Naveed; Mustafa, Ghulam; Naeem, Muhammad; Alotaibi, Bader Alhafi; Traore, Abou (Frontiers in Sustainable Food Systems, 2025)
The contemporary business environment places significant emphasis on sustainability, safety, and quality, particularly within the food processing industry. This sector is intrinsically linked to environmental stewardship, occupational health, and food safety, necessitating stringent standards to ensure compliance and enhance performance. As a result, management systems certifications such as ISO 14001 (Environmental Management System), ISO 45001 (Occupational Health and Safety Management System), and ISO 22000 (Food Safety Management System) have gained prominence. This paper analyzes the effect of ISO 14001, ISO 45001, and ISO 22000 on the food processing companies ‘environmental and financial performance. The analysis of fixed effect regressions applied to data from 19 food processing companies listed on the Pakistan Stock Exchange shows that management system certifications have a substantial positive impact on both environmental and financial performance. This evidence suggests that such certifications are key drivers of sustainable performance in the food processing sector. Additionally, factors such as company size, market share, and export ratio positively influence environmental performance. Conversely, real raw materials costs, real energy costs, and involvement in the food and beverage sector negatively affect environmental performance. In terms of financial performance, sales growth, current ratio, and asset turnover ratio show positive effects, while the dairy, food and beverages, and edible oil sectors have a negative impact.